Melindungi Sistem Login Pada Situs Web Dari Serangan Sql Injection - Zajuli T Bisri; Chaerur Rozikin (Informasi Interaktif, 2022)
Currently, internet users are increasingly widespread, especially for those who use a website. Security is the main thing that must be considered for the convenience and security of users. It is the job of website developers to make this a challenge. Because basically there is no guarantee that a website is safe. Therefore, the author will test the security of the web server, namely by performing SQL Injection. SQL Injection is a vulnerability or risk threat that can occur when an attacker has the ability to carry out activities to affect an SQL query that goes through a website to the database itself. In this study, implementing a PHP function, namely mysqli real escape string, which works to provide a backslash against a unique character or a special character before sending a query to mysql which can harm data, including from the SQL Injection attack. The results of this study are as a security warning of a website from attacks that want to break  into a website.